Terapia dziecka z rozszczepem kręgosłupa i wodogłowiem – studium przypadku - Malicka, Aurelia (Logopedia Silesiana, 2014)
The paper constitutes a presentation of diagnosis and therapy in a child after a intrauterine spina bifida surgery with recognized hydrocephalus. The author discusses the character of the disorder, pathomechanism and its results on the development of the child. The therapeutic techniques are presented and analyzed which aim at improving breathing, phonation and voice production as well as at stimulating both cerebral hemispheres. The author presents the results of the therapy and the case study highlights the accuracy of chosen methods.